Q-switching in EDFL cavity using Ti3AlC2 as saturable absorber / Suziana Omar ...[et al.] - Omar, Suziana; Musa, Baktiar; Harun, Sulaiman Wadi; Ahmed, Norizan; Zulkipli, Nur Farhanah; Jusoh, Zulzilawati; Abdul Rahman, Husna (UiTM Press, 2022)
In this paper, Titanium Aluminium Cloride (Ti3AlC2) is used as a saturable absorber (SA) to generate Q-switched pulses in an erbium-doped fibre laser (EDFL) cavity. The Ti3AlC2 film was prepared based mixing the material with polyvinyl alcohol (PVA) solution. It was added into the laser cavity by sandwiching the film between two fiber ferrules. By controlling the cavity's loss and gain, a stable Q-switched operation was achieved. When the pumping power was increased from 58.88 to 97.62 mW, the repetition frequency was increased from 59.52 to 67.52 kHz, resulting in the shortest pulse width of 3.3 µs. The Q-switched EDFL operated at a centre wavelength of 1560 nm, had a maximum pulse energy of 138.76 nJ, and a slope efficiency of 9.36 percent. The results demonstrate that Ti3AlC2 can be used as a SA for realizing a laser device for various applications including optical communications.